The Female and the Male Professional: Gender, Career and Expatriation Interfaces in Trajectory for Female Expatriates - Aline Mendonça Fraga; Elaine Di Diego Antunes; Sidinei Rocha-de-Oliveira (BBR: Brazilian Business Review)
While the organizational world has been experiencing the phenomenon of expatriation, the availability of mobile and international careers stand out. The differences in the expatriate experience are gendered, and few studies focus primarily on the experiences of women. This research aims to analyze the construction of the career trajectories of 19 Brazilian expatriate women, using as conceptual bases the interfaces of gender, career, and expatriation. The experiences of the participants come near to each other but compose unique trajectories, including in their personal life and professional field. The study highlights a way of being and acting in the work environment, understood as "the" model of a professional woman expatriate, who intercalates elements perceived as masculine and/or feminine. The construction of this trajectory is anchored by elements that build and influence it: personal characteristics, support and family influence, affective relationships, motherhood, professional plans and organizations in which they work, and countries of destination. With the results, possible paths are envisioned for other women seeking this experience, considering the foregrounded implications shown by this study.